Microbial contributions to plant growth and stress tolerance: Mechanisms for sustainable plant production - Neha Sharma; Lovely Mahawar; Arti Mishra; Benedicte Riber Albrectsen (Plant Stress)
Plant growth-promoting rhizobacteria (PGPRs) play a crucial role in enhancing plant development through a variety of direct and indirect mechanisms. These include the production of phytohormones, nitrogen fixation, phosphate solubilization, siderophore-mediated iron acquisition, and biocontrol of plant pathogens. Predominantly inhabiting the rhizosphere, PGPRs interact with plant roots via complex molecular and ecological processes involving signalling molecules, metabolite exchanges, and modulation of plant immune responses. Such interactions enhance nutrient uptake and stress tolerance but also contribute to long-term plant health and productivity across diverse environmental conditions. This review focuses on the genera Pseudomonas and Bacillus, which are extensively studied for their strong colonization abilities, metabolic versability, and demonstrated potential in improving crop resilience. Advances in microbial genomics, metagenomics, and high-throughput phenotyping have greatly enhanced our ability to identify, characterize, and apply beneficial microbes across a range of crop systems. However, key challenges remain, including limited understanding of native soil microbiotas, the functional outcome of microbiome-soil-plant interactions, and the development of agricultural practices that efficiently integrate microbial solutions. With potato (Solanum tuberosum) as a model crop, this review synthesizes current knowledge on PGRP-mediated growth promotion - primarily by Pseudomonas and Bacillus acting alone or in microbial consortia, identifies critical research gaps, and outlines future directions for the application of PGPRs in sustainable crop production.